To solve for \( d \) in the equation \( d^2 - 63 = -27 \), we will first isolate the term with \( d^2 \).
- Start by adding 63 to both sides of the equation:
\[ d^2 - 63 + 63 = -27 + 63 \]
This simplifies to:
\[ d^2 = 36 \]
- Next, take the square root of both sides. Remember to consider both the positive and negative square roots:
\[ d = \sqrt{36} \quad \text{or} \quad d = -\sqrt{36} \]
This simplifies to:
\[ d = 6 \quad \text{or} \quad d = -6 \]
- Therefore, the solutions for \( d \) are:
\[ d = 6 \quad \text{or} \quad d = -6 \]
Thus, the final answer is:
\[ d = 6, -6 \]